Cribriform Neuroepithelial Tumor Arising in the Lateral Ventricle. (July 2013) - Arnold, Michael A.; Stallings-Archer, Kandi; Marlin, Evan; Grondin, Ronald; Olshefski, Randal; Biegel, Jaclyn A.; Pierson, Christopher R.
Cribriform neuroepithelial tumor (CRINET) is a recently recognized central nervous system neoplasm that arises in the ventricles of young children and is characterized by primitive, non-rhabdoid SMARCB1-deficient cells with prominent cribriform architecture. We report a 14-month-old male who presented with signs of increased intracranial pressure. Neuroimaging revealed a large solid and cystic mass in the lateral ventricle. Tumor cells were small, primitive appearing, and arranged in cribriform and trabecular patterns with interspersed solid cellular areas. Rhabdoid cells were absent. Immunohistochemical staining showed no SMARCB1 (INI11, BAF47, hSNF5) expression and strong epithelial membrane antigen (EMA) immunoreactivity along luminal surfaces. Electron microscopy showed epithelial characteristics, including abundant basal lamina. Genetic analysis of the tumor revealed deletion of 1 SMARCB1 allele, while the other contained an intronic point mutation predicted to disrupt splicing. This case further illustrates the distinct histopathologic and molecular genetic features of CRINET and identifies distinctive ultrastructural features.